2020
DOI: 10.15294/jpii.v9i4.22973
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inquiry Learning with Scaffolding on Misconception of Light Material among Fourth-Grade Students

Abstract: The purpose of this study is to determine the effect of Inquiry learning with scaffolding to decrease the percentage of light material misconception among fourth-grade students. The method used was Quasi-experimental with a non-equivalent control group design. The population was fourth-grade students of the Surya Buana Islamic Elementary School, Malang. The result of Anacova showed that for the “Class” variable, the value of Significance (P-value) obtained was smaller than the α significance level of 0,00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…responsive learning conditions so that these activities are visible steps of the inquiry learning approach, namely orientation. The orientation stage of the inquiry approach explains the teacher preparing students to be ready and open to learning by exploring (Haidar et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…responsive learning conditions so that these activities are visible steps of the inquiry learning approach, namely orientation. The orientation stage of the inquiry approach explains the teacher preparing students to be ready and open to learning by exploring (Haidar et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The study by [24] found that e-scaffolding positively impacts students' academic ability by enhancing their conceptual understanding of the subject matter and the selection of strategies implemented when solving problems. E-scaffolding has also been proven to prevent misconceptions [25] and improve science process skills [26], problem-solving skills [27], and student learning outcomes [28]. Implementing e-scaffolding allows students to engage and acquire skills in independently solving complex problems [29].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, textbooks can cause students misconceptions (Suparno, 2013). It may underlie that misconceptions about light and vision are often found at the elementary school level (Haidar et al, 2020;Ravanis, 2019;Ravanis et al, 2009). Textbooks can include various representations to develop students' knowledge (Bergqvist et al, 2017).…”
Section: Introductionmentioning
confidence: 99%